Microbiological Testing of Gastric Aspirate Improves the Diagnosis of Pulmonary Tuberculosis in Unconscious Adults with TB Meningitis - Ahmad Rizal Ganiem; Lilya Wati Djung; Lidya Chaidir; Uni Gamayani (MDPI AG, 2020)
Conventional sputum collection for TB diagnosis is difficult in TB meningitis patients since most of them are admitted with decreased consciousness. It is assumed that unconscious patients swallow their sputum; therefore, gastric aspiration can replace sputum collection in unconscious patients. A prospective study was conducted to see whether examining gastric aspirate could increase the diagnosis certainty of pulmonary TB in such subjects. The inclusion criteria were age 18-60 years, decreased level of consciousness, and use of a nasogastric tube. Subjects who had taken antituberculosis drugs for more than 3 days were excluded. Gastric lavage was performed in the morning after an overnight fast. Specimens were examined for direct smear, culture, and rapid molecular testing. Demographic, clinical, chest X-ray, and laboratory data were also recorded. During the study period, 31 subjects were available. The positivity rates for microbiological tests were 19.3%, 41.9%, and 48.4% for smear, culture, and rapid molecular testing, respectively. All positive smears were confirmed by either culture or rapid molecular testing. Gastric lavage can be considered a tool for improving extraneural TB diagnosis in unconscious patients.